2014
DOI: 10.5194/acp-14-7807-2014
|View full text |Cite
|
Sign up to set email alerts
|

Organosulfates and organic acids in Arctic aerosols: speciation, annual variation and concentration levels

Abstract: Abstract. Sources, composition and occurrence of secondary organic aerosols in the Arctic were investigated at Zeppelin Mountain, Svalbard, and Station Nord, northeastern Greenland, during the full annual cycle of 2008 and 2010, respectively. Speciation of organic acids, organosulfates and nitrooxy organosulfates – from both anthropogenic and biogenic precursors were in focus. A total of 11 organic acids (terpenylic acid, benzoic acid, phthalic acid, pinic acid, suberic acid, azelaic acid, adipic acid, pimelic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 79 publications
4
90
0
Order By: Relevance
“…as (NH 4 ) 2 SO 4 or NH 4 HSO 4 (Seinfeld and Pandis, 2006). Furthermore, inorganic sulfate can react with organic aerosol species to form organosulfates (Liggio and Li, 2006;Surratt et al, 2007), which have also been observed in the Arctic (Hansen et al, 2014). The presence of sulfate also enhances the CCN activity in atmospheric aerosol samples (Quinn and Bates, 2011).…”
Section: A Massling Et Al: Atmospheric Black Carbon and Sulfate Conmentioning
confidence: 97%
“…as (NH 4 ) 2 SO 4 or NH 4 HSO 4 (Seinfeld and Pandis, 2006). Furthermore, inorganic sulfate can react with organic aerosol species to form organosulfates (Liggio and Li, 2006;Surratt et al, 2007), which have also been observed in the Arctic (Hansen et al, 2014). The presence of sulfate also enhances the CCN activity in atmospheric aerosol samples (Quinn and Bates, 2011).…”
Section: A Massling Et Al: Atmospheric Black Carbon and Sulfate Conmentioning
confidence: 97%
“…During winter and early spring, much of the OM may come from Eurasian fossil fuel sources (e.g., Behrenfeldt et al, 2008;Nguyen et al, 2013;Barrett et al, 2015), and it is mixed with sulfates and nitrates (Weinbruch et al, 2012). Organic acids and organosulfates measured in samples from Station Nord suggest that OM during October to April is from distant anthropogenic sources, whereas the year-round presence of organic sulfates in samples collected at Mount Zeppelin indicates contributions from local sources as well as long-range transport (Hansen et al, 2014). Tracers of secondary organic aerosol (SOA) production from BVOC oxidation have been found in the late spring and summer at Alert (Fu et al, 2009a, b) and in the Arctic marine boundary layer (Hu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tracers of secondary organic aerosol (SOA) production from BVOC oxidation have been found in the late spring and summer at Alert (Fu et al, 2009a, b) and in the Arctic marine boundary layer (Hu et al, 2013). During May-September, organic acids at Station Nord suggest evidence of a relatively high biogenic influence (Hansen et al, 2014). Summer observations from ships in the central Arctic Ocean (Chang et al, 2011) and the southeast Beaufort Sea (Kawamura et al, 2012), as well as spring samples from Alert (Fu et al, 2015), indicate OM from both marine and continental sources.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of molecular tracers for secondary organic aerosol (SOA) has indicated a contribution from secondary processes. In particular, tracers of isoprene, terpene, and fatty acid oxidation have been detected in summer aerosol at several Arctic sites, including Alert, Nunavut; Station Nord, Greenland; and Zeppelin, Svalbard [Fu et al, 2009;Kawamura et al, 2012;Fu et al, 2013;Hansen et al, 2014]. Sources of gas phase precursors to SOA are poorly characterized in Arctic summer but could include Arctic terrestrial [Schollert et al, 2014;Kramshoj et al, 2016] and marine emissions [Willis et al, 2016;Kim et al, 2017;Mungall et al, 2017].…”
Section: Introductionmentioning
confidence: 99%